2015
DOI: 10.1016/j.egypro.2014.11.870
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Double Differential Neutron Yields from Thick Aluminum Target Irradiated by 9 MeV Deuteron

Abstract: Double differential neutron yields from a thick aluminum target irradiated by 9 MeV deuterons were measured at the Kyushu University Tandem accelerator Laboratory (KUTL). An NE213 liquid organic scintillator (50.4 mm thick and 50.4 mm in diameter) was used as a neutron detector. Neutron yields from the target were measured at nine angles between 0° and 140°. The neutron energy spectra were obtained by means of an unfolding method using FORIST code with the response function of the NE213 scintillator calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We have carried out a series of measurements of doubledifferential neutron yields from thick targets irradiated by deuterons at the Kyushu University Tandem accelerator Laboratory (KUTL) [25][26][27][28][29][30]: carbon, aluminum, titanium, copper, niobium, and tantalum for bombardment energies of 5 and 9 MeV. In addition, double-differential thick target gamma-ray yields from carbon and aluminum irradiated by 5 and 9 MeV deuterons were measured at the same time.…”
Section: Thick Target Neutron Yields At Deuteron Energies Below 10 Mevmentioning
confidence: 99%
See 1 more Smart Citation
“…We have carried out a series of measurements of doubledifferential neutron yields from thick targets irradiated by deuterons at the Kyushu University Tandem accelerator Laboratory (KUTL) [25][26][27][28][29][30]: carbon, aluminum, titanium, copper, niobium, and tantalum for bombardment energies of 5 and 9 MeV. In addition, double-differential thick target gamma-ray yields from carbon and aluminum irradiated by 5 and 9 MeV deuterons were measured at the same time.…”
Section: Thick Target Neutron Yields At Deuteron Energies Below 10 Mevmentioning
confidence: 99%
“…The details of the experimental set up and procedure have been reported in Refs. [25][26][27][28][29][30].…”
Section: Thick Target Neutron Yields At Deuteron Energies Below 10 Mevmentioning
confidence: 99%
“…Howev-JRPR er, they were treated as background events in the neutron data analysis. As far as theoretical models are concerned, it was found that the intra-nuclear cascade of Liege (INCL) model [7] in PHITS [8] generally reproduce the DDTTNYs data of Al targets in both the shape and magnitude [9]. Also, it will be necessary to validate some reaction models used in PHITS using gamma-ray yield data for engineering design of deuteron accelerator facilities.…”
Section: Introductionmentioning
confidence: 99%